Estudo do comportamento de antena de microfita com substrato metamaterial - Silva, José Lucas da (2015)
This work aims to characterize microstrip antennas operating on microwave bands, specifically on their behavior between 6 GHz and 16 GHz with metamaterial substrate. These microstrip antennas allow the miniaturization of their structures, which is important to devices that use this antenna, considering their features such: low cost, accommodation facility and structure lightness. In addition to the metamaterials, which are made by geometrical, structures from common materials, such conductors, dielectrics, magnetics or even their combination. The main characteristic of the metamaterials is based on presenting special features of permissiveness and permeability, which are not found in natural materials, whose main effect is the negative refraction rate. By having those features, it is possible to use them in many optical and electromagnetism ways. The metamaterial theory is described and applied on this work as a way of microstrip antenna substrate in order to work the permissiveness and permeability related to the scope of propagation of electromagnetic waves. Some analysis parameters are observed such: resonance and distant field frequency, formulating the characterization and behavior of the observed microstrip antennas